Fabrication of silicon grating structures using interference lithography and chalcogenide inorganic photoresist - Min’ko, V.I.; Shepeliavyi, P.E.; Indutnyy, I.Z.; Litvin, O.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Application of inorganic photoresist based on chalcogenide films for fabrication of submicrometer periodic relief on silicon wafers was investigated. For this purpose, technological process of resistive two-layer chalcogenide-Cr mask formation on a silicon surface was developed, and silicon anisotropic etching was optimized, too. This technology has been used for the fabrication of high-quality diffraction gratings on Si (100) surface with symmetric triangular and trapezium grooves and two-dimentional periodic structures. Relief parameters and diffraction properties of the obtained structures and their dependences on etching time were determined